350 kHz large‐angle scanning of laser light using KTa1−xNbxO3 optical deflector. Issue 25 (1st December 2014) - Sakamoto, T.; Toyoda, S.; Ueno, M.; Kobayashi, J.
Abstract : A scanning frequency of 350 kHz is demonstrated with a full deflection angle of 95.8 mrad using a KTa1− x Nb x O3 (KTN) deflector. To suppress degradation of the deflection angle, the KTN chip is directly glued to metal block electrodes with conductive paste, and the temperature of the deflector is controlled so that the capacitance of the KTN chip remains constant.